Polyionic complex of single-walled carbon nanotubes and PEG-grafted-hyperbranched polyethyleneimine (PEG-PEI-SWNT) for an improved doxorubicin loading and delivery: development and in vitro characterization. (4th July 2017) - Farvadi, Fakhrossadat; Tamaddon, AliMohammad; Sobhani, Zahra; Abolmaali, Samira Sadat
Abstract: To take advantages of single-walled carbon nanotubes (SWNTs) for cellular delivery of chemotherapeutic agents (e.g. doxorubicin) in order to decrease general toxicities of doxorubicin (DOX) and to promote the efficacy, we aimed to develop a novel approach to stabilize SWNTs through consequent steps of oxidation and PEG-g-PEI polyionic complexation (PEG-PEI-SWNT). The DOX loading capacity of modified SWNTs was about 900%. Moreover, it showed an enhanced dispersibility in physiologic-stimulated medium. DOX release was prolonged, independent of dilution, and exhibited an acidic pH-stimulated release. Therefore, PEG-PEI-SWNT could be used for cancer chemotherapy in vivo .